2011
DOI: 10.1242/jcs.078030
|View full text |Cite
|
Sign up to set email alerts
|

A DNA-dependent stress response involving DNA-PK occurs in hypoxic cells and contributes to cellular adaptation to hypoxia

Abstract: SummaryDNA-dependent protein kinase (DNA-PK) is involved in DNA double-strand break (DSB) signalling and repair. We report that DNA-PK is activated by mild hypoxia conditions (0.1-1% O 2 ) as shown by (1) its autophosphorylation on Ser2056, and (2) its mobilisation from a soluble nucleoplasmic compartment to a less extractable nuclear fraction. The recruitment of DNA-PK was not followed by activation and recruitment of the XRCC4-DNA-ligase-IV complex, suggesting that DSBs are not responsible for activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 41 publications
(69 reference statements)
5
59
1
1
Order By: Relevance
“…We previously reported that DNA-PK expression was strongly reduced by the absence of HIF-1 α under both normoxic and hypoxic conditions (Wirthner et al , 2008 ), raising the possibility that DNA-PK might be the responsible kinase for H2AX phosporylation in chronic hypoxia. In line with this hypothesis, accumulation of DNA-PKcs, Ku70 and Ku80 following hypoxia and iron chelation have been demonstrated in a number of different cell lines (Ginis and Faller , 2000 ;Lynch et al , 2001 ;Um et al , 2004 ;Bouquet et al , 2011 ). DNA-PK has been shown to phosphorylate H2AX in different cell lines and in vivo in response to DNA damage (Stiff et al , 2004 ;Koike et al , 2008 ;An et al , 2010 ) under hypertonic conditions (Reitsema et al , 2005 ) and during apoptotic DNA fragmentation (Mukherjee et al , 2006 ).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We previously reported that DNA-PK expression was strongly reduced by the absence of HIF-1 α under both normoxic and hypoxic conditions (Wirthner et al , 2008 ), raising the possibility that DNA-PK might be the responsible kinase for H2AX phosporylation in chronic hypoxia. In line with this hypothesis, accumulation of DNA-PKcs, Ku70 and Ku80 following hypoxia and iron chelation have been demonstrated in a number of different cell lines (Ginis and Faller , 2000 ;Lynch et al , 2001 ;Um et al , 2004 ;Bouquet et al , 2011 ). DNA-PK has been shown to phosphorylate H2AX in different cell lines and in vivo in response to DNA damage (Stiff et al , 2004 ;Koike et al , 2008 ;An et al , 2010 ) under hypertonic conditions (Reitsema et al , 2005 ) and during apoptotic DNA fragmentation (Mukherjee et al , 2006 ).…”
Section: Discussionmentioning
confidence: 70%
“…DNA-PK has been shown to phosphorylate H2AX in different cell lines and in vivo in response to DNA damage (Stiff et al , 2004 ;Koike et al , 2008 ;An et al , 2010 ) under hypertonic conditions (Reitsema et al , 2005 ) and during apoptotic DNA fragmentation (Mukherjee et al , 2006 ). Of note, the hypoxic DNA-PK activation resulted in increased HIF-dependent gene expression (Bouquet et al , 2011 ). These data suggest that DNA-PK might be both upstream and downstream of HIF.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study (47) showed that DNA-PK was important for regulating HIF-1 stability and its target gene, GLUT1, under hypoxia (47). Taken together, these findings suggest that the tyrosine kinase domain of RON not only activates the intracellular signaling pathway, but also interacts with other nuclear proteins, HIF-1a, Ku70, and DNA-PKcs, when cancer cells are exposed to hypoxiainduced stress.…”
Section: Discussionmentioning
confidence: 96%
“…(i) La DNA-PK est impliquée dans des voies biochimiques autres que la réparation des cassures: maintien de la longueur des télo-mères, rôle dans le point de contrôle G2 après irradiation, méta-bolisme en réponse à l'insuline, phosphorylation de substrats qui ne participent pas à la réparation de l'ADN, contrôle de la dégradation du facteur de régulation de l'hypoxie, HIF-1␣ (Bouquet et al 2011 ;Kong et al 2011). Ces nouvelles données renforcent l'importance de la DNA-PK dans le maintien de l'homéostasie cellulaire et la réponse à divers stress mais paradoxalement compromettent l'intérêt thérapeutique d'un blocage de cette activité non spécifique aux cellules tumorales.…”
Section: Discussionunclassified